Immature platelets in COVID-19. (31st December 2023) - Wolny, Monika; Dittrich, Marcus; Knabbe, Cornelius; Birschmann, Ingvild
Abstract: Platelets play a critical role in immune response. Coronavirus disease 2019 (COVID-19) patients with a severe course often show pathological coagulation parameters including thrombocytopenia, and at the same time the proportion of immature platelets increases. In this study, the platelet count and the immature platelet fraction (IPF) of hospitalized patients with different oxygenation requirements was investigated daily over a course of 40 days. In addition, the platelet function of COVID-19 patients was analyzed. It was found that the number of platelets in patients with the most severe course (intubation and extracorporeal membrane oxygenation (ECMO)) was significantly lower (111.5 ∙ 10 6 /mL) than in the other groups (mild (no intubation, no ECMO): 203.5 ∙ 10 6 /mL, p  < .0001, moderate (intubation, no ECMO): 208.0 ∙ 10 6 /mL, p  < .0001). IPF tended to be elevated (10.9%). Platelet function was reduced. Differentiation by outcome revealed that the deceased patients had a highly significant lower platelet count and higher IPF (97.3 ∙ 10 6 /mL, p  < .0001, 12.2%, p  = .0003). Plain Language Summary: What is the context? Pathological coagulation is a feature of severe cases of COVID-19, with both bleeding complications and thrombosis. Patients with severe COVID-19 are frequently treated with extracorporeal membrane oxygenation (ECMO), which is often associated with bleeding complications. Platelets play an important role in blood clotting. The proportion of immature platelets has been characterized as hyperreactive and associated with high prothrombotic activity. In addition, they are discussed as predictors of COVID-19 disease severity. What is new? In grading the severity of disease in our patient cohort, we consider the required oxygenation measures. Thus, the focus is on severe cases requiring intubation and ECMO compared to moderate (intubation, no ECMO) and mild (no intubation, no ECMO) cases. What is the impact? This study focuses on severely ill patients who require ECMO treatment. Therefore, this study provides further evidence to use immature platelet fraction to predict the outcome of severe COVID-19 courses.